Infectious complications distribution following CLL1 CAR-T cell therapy for acute myeloid leukemiass - Jianmei Xu; Huan Zhang; Yifan Zhao; Xiaomei Zhang; Shujing Guo; Xiaoxue Shi; Xia Xiao; Hairong Lyu; Yu Zhang; Xiaoyuan He; Mingfeng Zhao (Cancer Immunology, Immunotherapy)
Abstract The CLL1-targeted chimeric antigen receptor T (CAR-T) cell therapy offers a novel therapeutic approach for refractory or relapsed acute myeloid leukemia (AML).The targeted elimination of tumor cells by CLL1 CAR-T therapy also induces cytotoxic effects on neutrophils, leading to a severe granulocytopenia, thereby significantly increasing the risk of infectious complications during CAR-T therapy. However, the infectious complications associated with this strategy have not been comprehensively investigated. The objective of this study was to evaluate the incidence rate of infectious complications within a 28-day period in a cohort of 51 patients who underwent CLL1 CAR-T cell infusion. Meanwhile, the univariate and multivariate analyses were employed to access the risk factors of infectious complications during CLL1 CAR-T therapy. The study observed a total of 46 infection events in 32 out of 51 patients (63%), with the median onset of infection occurring at 9 days following CAR-T cell infusion. The cumulative incidence of infection events within 28 days was 56.9% (95%CI: 50.4–61.3%), with bacterial and fungal infections being the most prevalent early infection events. The results of multivariate analysis revealed that a lower neutrophil counts prior to lymphodepletion chemotherapy (OR = 3.875, P = 0.041) and more severe complications of cytokine release syndrome (OR = 4.141, P = 0.037) were identified as independent risk factors associated with an increased likelihood of early infection events. This study examined the distribution of early infection events and identified potential risk factors, with the goal of offering guidance to physicians on implementing more effective intervention strategies to decrease treatment-related mortality rates and improve patient prognosis. This study has been registered in the Chinese Clinical Trial Registry (Trial registration number: ChiCTR2000041054).